Women and Men Municipal Managers Doing and Undoing Gender. (13th November 2020) - Bishu, Sebawit G; Heckler, Nuri
Abstract: Drawing on the literature from critical gender studies and feminist critiques of bureaucracy, we explore the demands for gender work created when women occupy traditionally masculine roles in municipal government management. The article traces the work performed when municipal managers and municipalities respond to gendered demands, maintain gender perceptions, and negotiate gendered expectations, collectively referred to as gender work. To examine this process, we apply inductive qualitative method to analyze 21 semistructured interviews with men and women municipal managers in southeast United States. Our study reveals gender work at different levels of organizational hierarchies and in multiple ways. We find that women CAOs perform masculine gender work to negotiate a place in municipal leadership. We also find that municipal governments and men CAOs do feminine gender work to cultivate an environment for women to occupy counterstereotypical roles. This study suggests that jobs, institutional rules and policies, informal arrangements, work structures, and individuals' private lives interplay to require gender work from women that is more complex and more demanding than that required of men in the same roles.